The Prohibition of Sexual Intercourse during Menstruation: An Interdisciplinary Study of Medicine, Fiqh, and Maqāṣid Al-Sharī'ah - Rosyidah, Umi; Nashrullah; Al Banna, Ahmad Hasan; Hj Mohiddin, Hjh Mas Nooraini (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya (https://uinsa.ac.id/fsh/facility), 2025)
Abstract: Menstruation is one of the crucial aspects in the study of women's jurisprudence that has legal implications for worship and marital relations. One of the prohibitions regulated in Islam is sexual intercourse during menstruation, which is explicitly explained in the Qur'an and hadith. This study aims to examine the prohibition from the perspective of medicine, fiqh, and maqāṣid al-sharī'ah. This research is a normative juridical study employing a literature review approach to classical Islamic references and contemporary scientific findings. This article finds that the ban on sexual intercourse during menstruation is not only based on sharia as a form of worship and prudence, but also has a strong medical basis. Medically, sexual intercourse during menstruation can pose various health risks, such as reproductive tract infections, fertility disorders, and an increased risk of transmission of sexually transmitted diseases. In fiqh, the prohibition is based on the Qur'an, hadith, and ijma'. From the perspective of maqāṣid al-sharī'ah, sexual intercourse during menstruation is contrary to the five principles of benefit. These findings demonstrate that Islamic teachings align with modern health principles, while also underscoring the importance of an interdisciplinary approach in comprehensively understanding Islamic law. Keywords: fiqh, menstruation, intercourse, health, maqāṣid al-sharī'ah. Abstrak: Menstruasi merupakan salah satu aspek penting dalam kajian fikih wanita yang memiliki implikasi hukum terhadap ibadah dan relasi suami istri. Salah satu larangan yang diatur dalam Islam adalah bersenggama saat haid, yang secara eksplisit dijelaskan dalam Al-Qur’an dan hadis. Penelitian ini bertujuan untuk menelaah larangan tersebut dari perspektif medis, fiqh dan maqāṣid al-sharī'ah. Penelitian ini adalah penelitian yiridis normatif dengan pendekatan studi literatur terhadap referensi keislaman klasik dan temuan ilmiah kontemporer. Artikel ini menemukan bahwa larangan bersenggama saat haid tidak hanya berlandaskan syariat sebagai bentuk ibadah dan kehati-hatian, tetapi juga memiliki dasar medis yang kuat. Secara medis, hubungan seksual saat haid dapat menimbulkan berbagai risiko kesehatan, seperti infeksi saluran reproduksi, gangguan kesuburan, dan peningkatan risiko penularan penyakit menular seksual. Secara fiqh, larangan tersebut didasarkan pada Al-Qur’an, hadis dan ijma’. Dalam perspektif maqāṣid al-sharī'ah, hubungan seksual pada masa haid bertentangan dengan lima prinsip kemaslahatan. Temuan ini menunjukkan bahwa ajaran Islam sejalan dengan prinsip-prinsip kesehatan modern, sekaligus menegaskan pentingnya pendekatan interdisipliner dalam memahami hukum Islam secara komprehensif. Kata Kunci: Fikih, haid, bersenggama, kesehatan, maqāṣid al-sharī'ah.